The P2X7 Receptor is an Important Regulator of Extracellular ATP Levels - Brandao-Burch, Andrea; Key, Michelle L.; Patel, Jessal J.; Arnett, Timothy R.; Orriss, Isabel R. (Frontiers in Endocrinology, 2012)
Controlled ATP release has been demonstrated from many neuronal and non-neuronal cell types. Once released, extracellular ATP acts on cells in a paracrine manner via purinergic receptors. Considerable evidence now suggests that extracellular nucleotides, signalling via P2 receptors, play important roles in bone homeostasis modulating both osteoblast and osteoclast function. In this study, we demonstrate that mouse osteoclasts and their precursors constitutively release ATP into their extracellular environment. Levels were highest at day 2 (precursor cells), possibly reflecting the high number of red blood cells and accessory cells present. Mature osteoclasts constitutively released ATP in the range 0.05-0.5pmol/ml/cell. Both osteoclasts and osteoblasts express mRNA and protein for the P2X7 receptor. We found that in osteoclasts, expression levels are 4-fold higher in mature cells relative to precursors, whilst in osteoblasts expression remains relatively constant during differentiation. Selective antagonists (0.1-100µM AZ10606120, A438079 and KN-62) were used to determine whether this release was mediated via P2X7 receptors. AZ10606120, A438079 and KN-62, at 0.1-10µM, decreased ATP release by mature osteoclasts by up to 70%, 60% and 80%, respectively. No differences in cell viability were observed. ATP release also occurs via vesicular exocytosis; inhibitors of this process (1-100µM NEM or brefeldin A) had no effect on ATP release from osteoclasts. P2X7 receptor antagonists (0.1-10µM) also decreased ATP release from primary rat osteoblasts by up to 80%. These data show that ATP release via the P2X7 receptor contributes to extracellular ATP levels in osteoclast and osteoblast cultures, suggesting an important additional role for this receptor in autocrine/paracrine purinergic signalling in bone.